2019
DOI: 10.1073/pnas.1817246116
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided design fine-tunes pharmacokinetics, tolerability, and antitumor profile of multispecific frizzled antibodies

Abstract: Aberrant activation of Wnt/β-catenin signaling occurs frequently in cancer. However, therapeutic targeting of this pathway is complicated by the role of Wnt in stem cell maintenance and tissue homeostasis. Here, we evaluated antibodies blocking 6 of the 10 human Wnt/Frizzled (FZD) receptors as potential therapeutics. Crystal structures revealed a common binding site for these monoclonal antibodies (mAbs) on FZD, blocking the interaction with the Wnt palmitoleic acid moiety. However, these mAbs displayed gastro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Our evidence on LINC00688 is in contrast with those reported in gastric, breast and colon cancers [ 48 ]. Therefore, further investigation is needed to verify the role of this lncRNA in ERG-positive prostate tumors, in which it is reported that the expression of cell cycle-related genes is negatively regulated by ERG [ 53 ]. Likewise, the lnc-SAYSD1-1 also bioinformatically allows to distinguish the ERG-positive from all the other subclasses of prostate cancer with a Gleason score ≤ 3+4.…”
Section: Discussionmentioning
confidence: 99%
“…Our evidence on LINC00688 is in contrast with those reported in gastric, breast and colon cancers [ 48 ]. Therefore, further investigation is needed to verify the role of this lncRNA in ERG-positive prostate tumors, in which it is reported that the expression of cell cycle-related genes is negatively regulated by ERG [ 53 ]. Likewise, the lnc-SAYSD1-1 also bioinformatically allows to distinguish the ERG-positive from all the other subclasses of prostate cancer with a Gleason score ≤ 3+4.…”
Section: Discussionmentioning
confidence: 99%
“…A phase Ib clinical trial in HER2 − breast cancer patients identified a four-gene signature (FBXW2, CCND2, CTBP2, and WIF1) as a potential predictive biomarker for the response to combined treatment with paclitaxel and vantictumab (Zhang et al, 2018). Structure guided design will likely help in generating more specific antibodies that target individual FZD receptors (Raman et al, 2019). Based on the available data, FZD6 and FZD7 seem obvious candidates for therapeutic intervention (Figure 1 and Table 1).…”
Section: Will Breast Cancer Patients Benefit From Drugs Targeting Thementioning
confidence: 99%
“…Inhibition of porcupine will shut down Wnt secretion [32]. Antibodies or molecular mimics could be used to interfere with ligand-receptor interactions [33]. Such strategies may also be developed towards coagonists such as the R-spondin family [34], molecules that amplify canonical signaling pathway activation [35].…”
Section: Fine-tuning Of Wnt Signaling Is Essential For Joint Healthmentioning
confidence: 99%